Nitrogen and sulfur codoped graphene quantum dots as a new fluorescent probe for Au3+ ions in aqueous media. Issue 130 (17th December 2015) - Yang, Tingting; Cai, Fei; Zhang, Xiaodan; Huang, Yuming
Abstract : The N and S codoped GQDs can be used as a promising label free fluorescent probe for the sensitive and selective detection of Au 3+ in aqueous media, which provides a new application of the functionalized GQDs to the detection of metal ions. Abstract : Nitrogen and sulfur codoped graphene quantum dots (N, S-GQDs) were facilely fabricated by a one-step hydrothermal treatment of citric acid as the carbon source in the presence of cysteine as the doping agent. The resulting N, S-GQDs were characterized by TEM, AFM, Raman, FT-IR, UV-vis, XPS and fluorescence spectroscopy. The N, S-GQDs display a luminescence quantum yield of 35.4%, which was about 14 times greater than that of the undoped graphene quantum dots (GQDs). The AFM image showed a typical topographic height of 0.5 to 1.5 nm with 1–4 graphene layers. The fluorescent emission spectra of N, S-GQDs display an excitation-dependent behavior, and the emission peaks shift from 413 to 440 nm on increasing the excitation wavelength from 310 to 380 nm. The N, S-GQDs possess a storage stability of at least 2 months and are stable in the presence of high concentrations of salt. Due to the strong specific reactivity between Au 3+ and amine groups on the N, S-GQDs, the addition of Au 3+ ions to the N, S-GQDs suspension results in the formation of gold nanoparticles, which strongly quench the fluorescence of N, S-GQDs. While, other common cations and anions result in negligible changes in the fluorescence of N, S-GQDs. On this basis, a sensitive fluorometric method for the detection of Au 3+ was developed that has a 50 nM detection limit and a linear range that extends from 0.1 μM to 50 μM. The method has been successfully used for the determination of Au 3+ in real aqueous samples and for gold content in auranofin.